2023
DOI: 10.1007/s40123-023-00702-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Function of Adiponectin in Diabetic Retinopathy

Abstract: Adiponectin, one of the most ubiquitous adipokines found in the blood, plays a major role in glucolipid metabolism and energy metabolism and regulation. In recent years, a growing body of research indicates that adiponectin also plays a significant role in diabetic retinopathy. In the present review, we specifically address the protective effects of adiponectin on the development and progression of diabetic retinopathy through improvement in insulin resistance, alleviation of oxidative stress, limiting of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 119 publications
1
5
0
Order By: Relevance
“…Immunohistochemical analysis showed weak positive retinal expression of VEGF (Figure 2 c), and TNF-α (Figure 3 c). The histopathological improvement noticed with adiponectin administration was in accordance with Deng et al [8] who demonstrated that adiponectin reduces oxidative stress, limits retinal inflammation, and prevents vascular remodeling and accelerated apoptosis of retinal capillary cells in diabetic rats.…”
Section: Serum Insulinsupporting
confidence: 87%
See 2 more Smart Citations
“…Immunohistochemical analysis showed weak positive retinal expression of VEGF (Figure 2 c), and TNF-α (Figure 3 c). The histopathological improvement noticed with adiponectin administration was in accordance with Deng et al [8] who demonstrated that adiponectin reduces oxidative stress, limits retinal inflammation, and prevents vascular remodeling and accelerated apoptosis of retinal capillary cells in diabetic rats.…”
Section: Serum Insulinsupporting
confidence: 87%
“…In subgroup II B [Adiponectin-treated Diabetic retinopathy]: serum insulin was significantly lower than group I and significantly higher than subgroup II A. Histopathological analysis is showed in Figure 1 (A) (B) (C) Figure 1a Immunohistochemical analysis of TNF alpha is showed in Figure 3 (A) (B) (C) Figure 3a: A photomicrograph of a retinal section of normal control group showing no reactions for TNF-α. ----------------------------------------------------------------------------------------------------------------------------------------------DISCUSSION Diabetic retinopathy is a serious diabetic complication that causes visual defects and even blindness, it is characterized by oxidative stress, inflammation, hypoxia and pathological angiogenesis [3,4] .The adipokine adiponectin, has anti-inflammatory, antioxidant and antiangiogenic effects [8,16] .…”
Section: Serum Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancing age is associated with a declining capacity for antioxidant defense mechanisms, leading to an accumulation of reactive oxygen species (ROS) within diverse ocular cell types. This surge in ROS levels precipitates oxidative damage, a hallmark of age-related ocular pathologies [91]. APN hormone has garnered increasing attention for its anti-oxidative properties within the ocular tissues.…”
Section: Adiponectin's Antioxidative Properties In Ocular Tissuesmentioning
confidence: 99%
“…Emerging research has demonstrated that APN exerts a multifaceted anti-oxidative influence on retinal structures, particularly in the context of ocular diseases such as AMD and DR. APN appears to modulate oxidative stress by downregulating ROS generation, mitigating lipid peroxidation, and bolstering antioxidant defense mechanisms. Additionally, APN's capacity to enhance ECs function and mitigate inflammation plays a pivotal role in its anti-oxidative effects, as inflammation and oxidative stress are often intertwined in ocular pathologies [90]. The intricate interplay between APN and oxidative stress pathways in retinal cells presents a promising avenue for future investigations and therapeutic interventions aimed at preserving visual health.…”
Section: Adiponectin's Antioxidative Properties In Ocular Tissuesmentioning
confidence: 99%